Pengaruh Webrooming terhadap Confident, Smart Shopping Feeling, User-generated Content, dan Search Process Satisfaction - Sri Hartini; S. Nurul Hidayati (Universitas Proklamasi 45, 2021)
Recently, many people are switching from conventional shopping to digital shopping. even so, people feel that online shopping is less secure. Finally, many consumers search for information through the internet before shopping at brick and mortar stores. This study investigates how webrooming affects consumers’ experience and determines the effect of webrooming on consumer confidence, smart shopping feeling, user-generated content, and search process satisfaction in the beauty industry. The population in this study were all the beauty industry consumers who experience webrooming in the shopping process. The total sample used in this study was 166 people using purposive sampling. The result obtained from this study finds that webrooming has a significant and positive effect on confidence, smart shopping feeling, user-generated content. Both factors, confidence and smart shopping feeling subsequently significant and have a positive effect on search process satisfaction.